The Influence of Reward System on Employees' Performance Among Non-Academic Staffs in Masterskill University College of Health Sciences - Asra Juziela, Md. Hashim (2011)
Employees are the most valuable asset to organizations. Employee's performance is the main factor in determining the organization's performance and ensuring the organization to run smoothly and successfully. In order to maintain a good employee's performance, an effective performance management is compulsory. The purpose of this study is to examine the relationship between reward system (monetary and non-monetary rewards) and employee's performance in Masterskill University College of Health Sciences (MUCH). A survey involving 91 executive and non-executive staff was carried out. Three monetary reward factors (basic pay, merit/cost of living, performance bonus) and four non-monetary reward factors (recognition, learning opportunity, challenging works and career advancement) were tested. The data was analyzed using SPSS version 19. Pearson Correlation Coefficient analysis was run and employed to examine the affect of reward systems on the performance of MUCH employees. The result from Pearson Correlation Coefficient revealed that there is a positive significant relationship between reward system(monetary and non-monetary rewards) and employee's performance. Based on the results, it can be concluded that employees' performance is influenced by both monetary reward and non-monetary reward at 57% and 69.8% respectively. This study proposes that HRM must review the important of monetary and non-monetary rewards which can affect the employee's performance in their organization. In view of the results, other implications and recommendations are also discussed.